2012
DOI: 10.1179/1743284712y.0000000045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing routes on evolution of texture heterogeneity in 2014 aluminium alloy deformed by equal channel angular pressing (ECAP)

Abstract: In the present study, the effect of the processing routes (A, BA, BC and C) of equal channel angular pressing (ECAP) on texture evolution has been investigated for different initial microstructural conditions of the 2014 Al alloy. The present study also features the issue of heterogeneity in texture evolution along the thickness of the ECAP processed sample as a function of the processing routes. A stronger texture evolution was observed in the solution treated (ST) conditions for most of the processing routes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…The texture evolution during ECAP strongly depends on the processing routes. Venkatachalam et al [19] reported that the texture developed for aluminum alloy in route A was stronger than in the other processing routes due to the monotonic nature of strain path for this route. The texture resulting from ECAP following these four routes is governed by three factors: the applied deformation (which depends on the die configuration (Φ) and the number of passes (N)), the deformation mechanism (slip and twinning systems) and the initial texture.…”
Section: Introductionmentioning
confidence: 99%
“…The texture evolution during ECAP strongly depends on the processing routes. Venkatachalam et al [19] reported that the texture developed for aluminum alloy in route A was stronger than in the other processing routes due to the monotonic nature of strain path for this route. The texture resulting from ECAP following these four routes is governed by three factors: the applied deformation (which depends on the die configuration (Φ) and the number of passes (N)), the deformation mechanism (slip and twinning systems) and the initial texture.…”
Section: Introductionmentioning
confidence: 99%
“…Texture evolution during deformation via routes B A and B C were found to be nearly similar. On an average, textures measured at the mid plane of ECAP billets, showed that the components B/ B and A Ã 1 showed the highest intensities when deformed by routes A, B A and B C , while A Ã 2 and C components showed highest intensities when deformed by route C. 24) In another Al alloy AA2195, Suresh et al 26) observed that up to 3rd pass by route A, the components A Ã 1 , A Ã 2 , and B/ B exhibited highest intensities while after the 4th pass A Ã 2 and C components exhibited highest intensities. Skrotzki et al have extensively studied the heterogeneity of ECAP textures in Al, Ni, Cu and Ag 6,14,16,17,22,27) (Fig.…”
Section: Equal Channel Angular Pressing (Ecap)mentioning
confidence: 90%
“…After 3rd pass, the B/ B components were the strongest, a characteristic signature of low SFE material. 23) Studies were also carried out to investigate the evolution of ECAP textures in engineering alloys of aluminium, namely the AlCu alloy (AA2014) 24,25) and it was revealed that the evolution of texture was strongly dependent on the starting microstructures and processing routes. The starting material in aged condition developed weaker textures compared to the solution treated samples, after 5 passes of ECAP, which was attributed to higher scattering of strain during deformation by the fine precipitates in the aged samples.…”
Section: Equal Channel Angular Pressing (Ecap)mentioning
confidence: 99%
“…При увеличении числа проходов постепенно достигается насыщение плотности дислокаций, что снижает подвижность дислокаций и способст вует лишь незначительному увеличению твердости. Такой феномен представляет собой распространенное явление и согласуется с результатами других исследований, описанных в литературе [26]. Что касается маршрутов деформации, на рис.…”
Section: результаты исследования и их обсуждениеunclassified